A COMPREHENSIVE SYSTEMATIC REVIEW OF THE ASSOCIATION BETWEEN IRON DEFICIENCY ANAEMIA AND OCCULT GASTROINTESTINAL BLEEDING - Jeffy Marta (International Medical Journal Corp. Ltd, 2026)
Introduction: Iron deficiency anaemia (IDA) constitutes the most prevalent nutritional deficiency disorder worldwide. In adult men and postmenopausal women, chronic occult gastrointestinal (GI) blood loss represents the dominant pathological mechanism rather than dietary insufficiency. Occult GI bleeding denotes haemorrhage detectable only indirectly through faecal occult blood testing or through emerging iron deficiency. This systematic review synthesised and critically appraised primary evidence linking IDA to occult GI bleeding, determined diagnostic yield of investigative modalities, and identified predictors of bleeding lesions. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible designs comprised randomised controlled trials, cohort, case-control, cross-sectional and observational studies. Two reviewers independently performed study selection, data extraction and quality appraisal using design-matched risk-of-bias instruments (RoB 2, ROBINS-I, Newcastle-Ottawa Scale, QUADAS-2). Synthesis was narrative with structured tabulation across fourteen prespecified outcome domains. Results: Thirty-five primary studies encompassing >1.8 million participants met eligibility. Bidirectional endoscopy diagnostic yield for bleeding-potential lesions ranged from 35.0% to 76.2%. Small-bowel capsule endoscopy after negative bidirectional examination yielded pathology in 50.0–72.0%; in a prospective multicentre trial, small-bowel lesions (50.0%, 95% CI 42.2-57.7) significantly exceeded upper GI (28.2%, p<0.001) and colonic (20.0%, p<0.0001) lesions, altering management in 52.3%. IDA demonstrated strong malignancy association: GI cancer odds within one year were 4.47-fold higher (95% CI 4.14-4.82); IDA conferred higher adjusted colorectal cancer odds than rectal bleeding (aOR 2.2, 95% CI 2.0-2.3, p<0.01); young-onset colorectal cancer cumulative incidence was 0.45% with IDA versus 0.05% without (HR 10.81, 95% CI 8.15-14.33). Independent predictors included abdominal symptoms (OR 8.3), age >50 years (OR 4.4) and haemoglobin <9 g/dL (OR 3.0), yielding PPV 87% and NPV 93.5%. Quantitative faecal haemoglobin with IDA and age stratified one-year colorectal cancer risk from <1% to 30% (95% CI 19.4-41.0). Anticoagulant exposure carried strongest bleeding risk (RR 4.2, 95% CI 2.9-6.2). Colonoscopy delay >90 days independently impaired survival (adjusted HR 1.28, 95% CI 1.07-1.53, p=0.01). GRADE certainty was moderate for diagnostic-yield and oncological-risk domains. Discussion: IDA constitutes a sentinel biomarker of structural luminal pathology with malignancy discriminatory power exceeding symptom-based referral criteria. The small bowel represents the most frequent location of bleeding-capable lesions yet remains un-interrogated by bidirectional endoscopy. Faecal occult blood testing lacks sufficient sensitivity as a rule-out instrument; however, quantitative faecal haemoglobin retains risk-stratification value. Diagnostic latency independently determines survival outcomes. Conclusion: IDA demonstrates robust, reproducible association with occult GI bleeding and luminal malignancy. Bidirectional endoscopy should remain first-line in all adult men, postmenopausal women, and symptomatic premenopausal women; however, small-bowel predominance supports earlier capsule endoscopy deployment in negative bidirectional examinations or refractory anaemia. Faecal haemoglobin should serve as risk-stratification adjunct rather than gatekeeper, and diagnostic interval should be a quality metric. National pathways should adopt integrated risk models combining age, sex, haemoglobin, ferritin and quantitative faecal haemoglobin; capsule endoscopy capacity should be expanded; and standardised definitions are needed for future quantitative pooling.